Ten-Year Antibody Persistence and Booster Response to MenACWY-TT Vaccine After Primary Vaccination at 1-10 Years of Age. Issue 6 (2nd June 2020) - Vesikari, Timo; Peyrani, Paula; Webber, Chris; Van Der Wielen, Marie; Cheuvart, Brigitte; De Schrevel, Nathalie; Aris, Emmanuel; Cutler, Mark; Li, Ping; Perez, John L.
ABSTRACT: This phase 3B, open-label, extension study (NCT01962207) evaluated long-term persistence of antibodies induced by the quadrivalent meningococcal vaccine conjugated to tetanus toxoid (MenACWY-TT) compared with the meningococcal serogroup C vaccine conjugated to CRM (MenC-CRM) and the quadrivalent meningococcal polysaccharide vaccine (MenACWY-PS) 6 to 10 y after primary vaccination in toddlers (aged 1–<2 y; MenACWY-TT and MenC-CRM) and children (aged 2–<11 y; MenACWY-TT and MenACWY-PS). Antibody responses against meningococcal serogroups A, C, W, and Y were assessed by serum bactericidal antibody assays using rabbit (rSBA) or human (hSBA) complement. A MenACWY-TT booster dose at Year 10 was given to all eligible subjects regardless of the primary vaccine received. At Year 10, the percentages of subjects with rSBA titers ≥1:8 for serogroups A, C, W, and Y were as follows: MenACWY-TT (toddlers), 65.6%, 82.8%, 31.3%, 43.8%, respectively; MenC-CRM, 88.2% for serogroup C; MenACWY-TT (children), 88.9%, 84.1%, 67.1%, 65.9%; and MenACWY-PS, 28.6%, 81.0%, 23.8%, and 23.8%. Corresponding percentages for hSBA titers ≥1:4 were as follows: MenACWY-TT (toddlers), 31.1%, 91.9%, 44.4%, 41.4%; MenC-CRM, 93.8% for serogroup C; MenACWY-TT (children), 34.8%, 91.1%, 61.2%, 72.6%; and MenACWY-PS, 33.3%, 100.0%, 26.3%, and 44.4%. One month after the MenACWY-TT booster, the percentage of subjects with vaccine response ranged from 75.7% to 100.0% across serogroups in all study groups. Postbooster vaccine responses were generally comparable between groups across serogroups. No new safety signals were identified. Antibody responses persisted 10 y after MenACWY-TT vaccination. The MenACWY-TT booster dose was well tolerated and elicited robust immune responses.